Sensitivity and Specificity of Postmortem CT for Detection of Thoracic Injury - Komet Kosawiwat; RathachaiKaewlai; Pinporn Jenjitranant; Wisarn Worasuwannarak (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: Postmortem CT (PMCT) can help conventional autopsy in determining the cause of death andfinding injury to various organs. Since injuries among several vital organs in the thorax can cause death, thisresearch aims to assess the performance of PMCT in detecting injuries of the thoracic cavity organs.Materials and Method: A total of 56 dead bodies by unnatural traumatic death who underwent PMCTbefore autopsy were collected. Thoracic traumatic findingsfrom PMCT were compared with data obtainedfrom conventional autopsy wherethe autopsy was the reference standard and calculated for sensitivity,specificity, PPV, NPV, and accuracy.Results:Findings in which PMCT showed high sensitivity included air (100%) and fluid (86.67%). Intermsof bone fracture, sensitivity and accuracy were79.18% and 88.69%, respectively, especially for T-spinefractures (sensitivity 92.31%, accuracy 87.50%) and clavicle fractures (sensitivity 90%, accuracy 89.29%).For rib fractures, PMCTexhibited moderate to high sensitivity (68.18-91.67%) and high accuracy (78.57-98.21%). For soft tissueinjuries, PMCT had high specificity (99.21%), but low sensitivity (34.94%).Conclusion: PMCT is useful in detecting thoracic injuries in conjunction with the conventional autopsy byhelping to diagnose bone fractures, abnormal air, and fluid with high sensitivity and specificity.